Construction of Strategic Early-Warning System in Cyberspace - Zhuang Honglin, Yao Le, Wang Sheng, Gu Jiaxiang, Wu Ye, Xie Kai (《中国工程科学》杂志社, 2021)
Cyberspace strategic early-warning is a monitoring and warning system that is established by a country or group for early detection, tracking, identification, and notification of incoming major cyber attacks or the spreading destruction of powerful viruses. It’s an important component of a national security defense system. The implementation of the national cyber development strategy in China requires high attentions to the construction of a cyberspace strategic early-warning system. This study analyzes the major characteristics and basic requirements of strategic early-warning in cyberspace, and studies four major warning styles: security vulnerabilities, security threats, intrusion attacks, and abnormal behaviors warning. It also emphasizes four key projects, namely cyberspace surveying and mapping system, vulnerability collection and early-warning platform, threat intelligence perception and push system, as well as security monitoring and comprehensive early-warning system, after summarizing the construction of strategic early-warning and monitoring systems in cyberspace in China and abroad. Furthermore, we propose several countermeasures and suggestions, including strengthening high-level coordination, focusing on multi-source data integration, establishing professional earlywarning agencies, conducting regular security assessments, and implementing threat and early-warning grading mechanisms.